Role of Alcian blue (pH 2.5) histochemical stain in diagnostic thyroid pathology: how far is it helpful? - Palo, Seetu; Biligi, Dayananda S. (International Journal of Research in Medical Sciences, 2017)
Background: Controversies and pitfalls are well-known in diagnostic thyroid pathology. Since, the luminal surface of neoplastic thyroid follicular cells is said to be covered by a glycoproteinaceous material, there is a need to investigate the efficacy of mucin stains like Alcian blue (pH 2.5), which can be used as an adjunctive tool in difficult cases. Methods: 60 thyroidectomy specimens, received at Department of Pathology, were included in this retrospective analytical study. Alcian blue histochemical (pH 2.5) staining was done on representative sections and assessed for positivity. Results: Of the 60 cases analysed, all cases of papillary/nodular hyperplasia (n=10), follicular adenoma (n=14), follicular carcinoma (n=4) and medullary carcinoma (n=1) were negative for Alcian blue. Only 3/16 (18.7 %) cases of classical papillary carcinoma and 2/15 (13.3%) cases of follicular variant of papillary carcinoma showed positivity. Conclusions: We got statistically insignificant results with Alcian blue (pH 2.5) staining, making it unreliable in diagnostic thyroid pathology.